Intradermal delivery of modified mRNA encoding VEGF-A in patients with type 2 diabetes - Gan, Li-Ming; Lagerström-Fermér, Maria; Carlsson, Leif G.; Arfvidsson, Cecilia; Egnell, Ann-Charlotte; Rudvik, Anna; Kjaer, Magnus; Collén, Anna; Thompson, James D.; Joyal, John; Chialda, Ligia; Koernicke, Thomas; et al. (Nature communications, 2019)
Chemically modified mRNA is an efficient, biocompatible modality for therapeutic protein expression. We report a first-time-in-human study of this modality, aiming to evaluate safety and potential therapeutic effects. Men with type 2 diabetes mellitus (T2DM) received intradermal injections of modified mRNA encoding vascular endothelial growth factor A (VEGF-A) or buffered saline placebo (ethical obligations precluded use of a non-translatable mRNA control) at randomized sites on the forearm. The only causally treatment-related adverse events were mild injection-site reactions. Skin microdialysis revealed elevated VEGF-A protein levels at mRNA-treated sites versus placebo-treated sites from about 4–24 hours post-administration. Enhancements in basal skin blood flow at 4 hours and 7 days post-administration were detected using laser Doppler fluximetry and imaging. Intradermal VEGF-A mRNA was well tolerated and led to local functional VEGF-A protein expression and transient skin blood flow enhancement in men with T2DM. VEGF-A mRNA may have therapeutic potential for regenerative angiogenesis. Chemically modified mRNA is a new approach for therapeutic protein expression that could be applied to angiogenesis. Here the authors show in a phase 1 clinical trial that a modified mRNA encoding VEGF-A is well tolerated in patients with type 2 diabetes.